Keberkesanan Penyelaras Pembangunan di Daerah: Kajian Kes pada Mesyuarat Jawatankuasa Kerja Tindakan Daerah Padang Terap - Iswan, Rinaldi (2012)
This study aims to explore aspects of management in rural development coordination. Convergence studies provided to coordination of rural development in the District of Padang Terap that adjusted by the District Office of Padang Terap through the Local Executive Committee Meeting. The main focus of this study is to know the effects that arising as a result of the coordination is done, whether coordination activity has effect for increase progress of project development, as well as to handle or find the solution of some problems, complaints and suggestions from the community. This study used the descriptive qualitative method, in which the study is the result of observations made during his meeting coordination. While the "content analysis" is used to identify the local development agenda of Padang Terap District by examining three (3) of the minutes of Local Executive Committee Meeting start from July to October 2012. Results of the study to get the coordination done by District Office of Padang Terap through the Local Executive Committee Meeting showed a favorable effect on the progress activity development projects and problem solving in the District of Padang Terap.